Comparative Study of Egg Quality Traits of Sasso Chicken Breed under Different Management Systems and Phenotypic Correlation of Egg Parameters in Ethiopia - Bekele , Berhanu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study was conducted to evaluate the egg quality traits of Sasso chicken breed under different managements. For the experiment 160 fresh eggs form differently managed Sasso chickens (100 from on-station and 60 from on-farm) were randomly taken. The fresh eggs collected from farmers in Yirgalem were brought to Hawassa University poultry farm for quality measurement and the eggs collected from poultry farm of College of Agriculture in Hawassa University were separately determined. The recorded data was analyzed using SAS (ver. 9.4). Management system difference has a significant influence on more than half of studied external traits such as egg weight, egg length, egg width, shell thickness and egg surface area. The Sasso chickens managed under intensive system had significantly (p<0.05) higher mean egg weight (59.0g), egg length (57.5mm), egg width (42.2mm) and egg surface area (84.7mm2) than the same chicken breed reared under farmers management system. There was a significant difference in albumen weight, albumen height, yolk height, albumen ratio, yolk index, yolk albumen ratio and Hough unit for the eggs collected from the Sasso chickens under different management system. Egg weight has a highly significant and strong positive (p<.0001) phenotypic correlation with egg surface area (0.99), egg length (0.65), egg width (0.72) and shell weight (0.52). Albumen weight has significant correlation with all the studied internal egg quality parameters. It has the negative correlation with yolk ratio (-0.14) and yolk albumen ratio (-0.69). There was a variation for egg quality traits of Sasso chicken in different management systems where the on-station management system is better.